Elite Sport Development : Policy Learning and Political Priorities - Green, Mick, Houlihan, Barrie (Routledge, 2005)
Elite Sport Development addresses important sport policy questions and explores the emergence, development and current status of elite sport development policy with detailed examination of Australia, Canada and the UK. The sports compared are swimming, track and field athletics, and sailing.